PENGARUH DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK KULINER TRADISIONAL (STUDI PADA KONSUMEN GEN Z DI KOTA TOMOHON) - Poluan, Jane; Karuntu, Merlyn Mourah; Samadi, Reitty Lilyanny (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
Marketing is a dynamic business activity because it always changes from time to time. In the current industrial era 4.0, marketing is required to adopt digitalization so that digital marketing is one of the strategies that need to be implemented. In digital marketing, there are several strategies used, including content marketing and influencer marketing. These two variables were examined in purchasing decisions for traditional culinary products with respondents being gen Z consumers who are a very tech-conscious generation. The ease of existing technology, with various platforms that feature interesting content and influencers to offer traditional culinary products should be able to increase positive purchases, especially among gen Z consumers. The results found that digital marketing measured through content marketing and influencer marketing variables simultaneously influenced the purchasing decisions of Gen Z to buy traditional culinary in Tomohon City. Partially, it was found that informative, valuable, unique, and smart content marketing has a significant effect on purchasing decisions. Likewise, influencer marketing partially has a significant influence on purchasing decisions, where the influencers in question are influencers who meet the expectations of Gen Z, influencers who are able to help Gen Z decide on purchases, and influencers who are confident in promoting products.